Building capacity in indigenous governance: Comparing the Australian and American experiences. Issue 1 (24th October 2019) - Hendrix, Burke A.; Delaney, Danielle; Witmer, Richard C.; Moran, Mark; Sanders, Will; Ganter, Elizabeth
Abstract: This paper compares key aspects of governance structures for Indigenous populations in the United States and Australia. The paper focuses on policy coordination and administration, in particular the nodes of decision‐making in the two countries in relation to government contracting and accountability. The U.S. approach to funding Indigenous organizations stems from the 1975 Indian Self‐Determination and Education Act and its subsequent expansions. Through the development of contracting into permanent compacting via block grants, this approach builds established nodes of Indigenous government and facilitates whole‐of‐government coherence at the level of the American Indian tribe. The U.S. approach seems correlated with better performance and may lighten bureaucratic loads over the long term. The Australian model, on the other hand, seeks to create whole‐of‐government coherence through top‐down financial accountability in a way that hampers the development of Indigenous political capacity. The paper traces the development of these practices through time and illustrates how they contribute to the fragmentation rather than growth of Indigenous political capacities. It suggests ways the Australian model could be improved even in the absence of fundamental reform by drawing on the contracting‐to‐compacting framework of longstanding U.S. practices. Abstract : We compare models for funding Indigenous organisations in the United States and Australia. The U.S. approach encourages nodes of Indigenous governance via permanent compacting, and seems correlated with better performance. The Australian approach, on the other hand, pursues whole‐of‐government coherence via unpredictable short‐term contracts that fragment Indigenous political capacities.